PERJALANAN PERILAKU ORGANISASI: Suatu Tinjauan Perspektif Sejarah - Cokorda Gede Putra Yudistira; I Ketut Santra (Soshum: Jurnal Sosial dan Humaniora, 2014)
The erection of the Pyramids in Egypt, the Great Wall in China, the Taj Mahal India including Borobudur can not be separated from the countless people who worked day and night in a very long and tiring. We need a flashback of how individuals, groups and organizations behave from ancient times to the organization and postmodern society today. With a historical perspective one can explain fenemona now well and based on theory and previous evidences. The purpose of this paper is intended for, first to understand the major trends that make individuals, groups and organizations behave in a certain way expected. Second is about how, methods, concepts that appear in encouraging individuals, groups and organizations behave from each era through a historical overview. The conclusions of this paper are: the ways humans behave and behavioral organization have been studied since the time of Plato, it has been research topics and seminars research in the field of behavioral research organization. Efforts attempted to understand the behavioral organization can be done by understanding the historical review, studying that has ever been done by the figures of his time. Each figure proposed the idea in response to the situation of his time. Choosing and strengthening the suitable me that are by sorting our and storing the undesired ones.